Propuesta metodológica de Human Anatomy Atlas para el aprendizaje de anatomía humana con estudiantes de sexto semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología, periodo octubre 2021 – marzo 2022 - Guaranda Ramirez, Edwin Geovanny (2022)
As interactive multimedia systems evolve, with 3D atlas applications, innovative methodological proposals are presented that promote interaction between the user and the different study contents, necessary tools for learning theoretical and complex subjects. Therefore, the objective of this research was "To design the methodological proposal of Human Anatomy Atlas to facilitate the learning of Human Anatomy" because, in Higher Education Institutions (HEI), teachers still use traditional methodologies such as the master class, which generates short-term knowledge. In this sense, the methods according to the approach are quantitative, non-experimental design, according to its level: diagnostic, descriptive, and explanatory, as well as the place: bibliographic and field. To compile the results of the proposal and the problem, a survey with its instrument, the questionnaire, was applied to 20 sixthsemester students of the Pedagogy of Experimental Science: Chemistry and Biology career. To conclude t the design of the methodological proposal of Human Anatomy Atlas facilitated the learning of Human Anatomy in 90% according to the perception of those surveyed, a virtual tool that invites them to explore, recognize and experience the parts of the human body really from three-dimensional models. Therefore, it was suggested to teachers and students to use the methodological proposal of the Human Anatomy Atlas as an essential resource to develop longterm knowledge from methodologies focused on 3D images.